UTILITY OF MIDDLE CEREBRAL ARTERY DOPPLER IN THE DIAGNOSIS OF FETAL ANEMIA: AN OBSERVATIONAL STUDY - KUMARI AMRITA; GAUTAM MUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives are to assess the association between abnormal middle cerebral artery (MCA) Doppler findings (multiples of the median [MoM] >1.5) in the late third trimester (After 32 weeks of gestation) and neonatal hemoglobin levels and to evaluate its diagnostic accuracy in detecting anemia at birth. Methods: This retrospective observational study was conducted over a period of 1 year (May 2024–April 2025) at a tertiary care hospital. A total of 100 antenatal women with risk factors such as Rh isoimmunization, hydrops fetalis, or fetomaternal hemorrhage were enrolled. MCA Doppler was performed during the late third trimester (≥32 weeks gestation). Neonatal hemoglobin value was recorded at birth, and values below 2 standard deviations for gestational age were classified as anemic. Data were analyzed for correlation between Doppler findings and neonatal outcomes, including anemia and neonatal intensive care unit admission. Results: Of 100 cases, 34% had abnormal Doppler (MoM >1.5), and 31% of neonates were anemic. A statistically significant association was found between Doppler-positive status and neonatal anemia (Pearson Chi-square=49.795, p<0.001). Sensitivity and specificity of the Doppler test were 83.9% and 88.4%, respectively. The diagnostic performance of MCA Doppler for predicting neonatal anemia demonstrated a sensitivity of 87 %, specificity of 90 %, positive predictive value of 79 %, negative predictive value of 94%, and an overall accuracy of 89%. Conclusion: MCA Doppler is a simple, safe, and effective tool for antenatal detection of fetuses at risk of anemia, facilitating timely clinical preparedness at birth.